An inclined stepped plate transducer for ultrasonic applications - Pham , Huy Tuan (Journal of Technical Education Science, 2016)
A desire of ultrasonic devices with large working surfaces for industrial applications has drawn considerable attention from researchers. Many extensive radiators have been proposed and developed for various applications in the last few decades. However the design methodology for those devices is still a troublesome process and only works with some traditional profiles. In this research, an effective design method of a new i-stepped plate ultrasonic transducer is developed by using a genetic algorithm optimization scheme and ﬁnite element analyses. A possible application of food dehydration to dry heat sensitive materials and high-quality dry products has been recommended. Prototypes of the transducer are fabricated by a numerical control machining process. The effect of the ultrasonic field generated by the proposed design is investigated via a drying experiment of carrots.